Cr(V)–Cr(III) in-situ transition promotes ROS generation to achieve efficient cancer therapy. (September 2021) - Chen, Mingkai; Huang, Xiaoting; Shi, Huatian; Lai, Jie; Ma, Li; Lau, Tai-Chu; Chen, Tianfeng
Abstract: The development of metal-based anticancer drugs is of considerable interest and significance in inorganic medicine. In contrast to noble metal-based small molecules, the anticancer property of earth abundant metal-based small molecules is much less explored which are usually essential trace element for the human body. Among earth abundant metals, chromium (Cr) in the +3 valent is an essential trace element for the human body to low down the blood lipids and maintain the blood sugar; on the other hand, Cr(VI) are known to be highly toxic due to their oxidation power. To design stable high-valent Cr small molecules to construct Cr(high-valent)-Cr(III) in-situ transition system to achieve low-toxic and highly efficient anti-cancer therapy is a very desirable approach. Herein we report the Cr(V)–Cr(III) in-situ transition system promotes ROS generation to achieve efficient cancer therapy in vivo and in vitro . To the best of our knowledge, these Cr-based small molecules are the first stable Cr(V) compounds with potent anticancer efficacy, especially towards malignant cancers.